Perícia Contábil – Áreas De Atuação De Peritos (as) Contadores (as) Da Região Norte Do Brasil - Bezerra, Matheus Rodrigues (Universidade Federal do Tocantins, 2022)
The accounting expertise aims to clarify doubtful facts about the assets, to assist justice in the fair resolution of disputes and / or to resolve conflicts between parties. Considering the importance of the accounting expertise and the accountant expert, who is the one who carries out this work, the objective of this research arose to identify the areas of expertise of the experts in the Northern Region of Brazil, quantifying the number of professionals in the fields of activity described in the National Register of Accounting Experts (CNPC). The data were collected at CNPC, on the website of the Federal Accounting Council, the survey sample is the experts from the seven states in the region who were part of the registry until the end of 2019. The information extracted from the registry was: areas of expertise of the experts and their respective registration status. The results indicate that there are 180 registered experts who work in the region, which is divided into seven states: Acre, Amapá, Amazonas, Pará, Rondônia, Roraima and Tocantins. It should be noted that the areas of activity with the largest number of qualified professionals are, respectively: accounting, financial, tax, labor, other, company valuation and, lastly, judicial recovery and bankruptcy. It was also found through the results a much higher number of professional men in expertise in relation to women, in none of the seven states of the region the number of experts is greater than that of experts. This study concludes that despite the fact that women reduce inequalities between genders every day, in some areas such as accounting expertise, this disparity is still large.